Russian and International Law: Elements of Historical Continuity and Change study aid - Ragozin Historian Associate Professor of Tomsk Polytechnic University, Candidate of historical sciences (TPU Publishing House, 2022)
This teaching aid meets the needs of international students of non-legal specialties who study 'Fundamentals of Law' and 'Introduction to Russian Law'. It touches upon the most general issues of jurisprudence, such as its subject, methodology, functions, and place among other humanities, the concept and nature of law, its place in the system of social norms, etc. All material includes references to current regulatory legal acts and is adapted for assimilation by students from abroad. The teaching aid may be useful also to all those interested in Russian law.